Fluoride Sorption Onto a Steam‐Activated Biochar Derived From Cocos nucifera Shell. Issue 2 (10th December 2015) - Halder, Gopinath; Khan, Anoar Ali; Dhawane, Sumit
Abstract : Fluoride‐contaminated water and its potential menace to the human being has been of enormous environmental concern toward exploration of significant remedial measures. The present investigation focused on the removal of fluoride from synthetic wastewater using superheated steam activated biochar (SAB) derived from Cocos nucifera shell. The experiments were carried out under the influence of three operational parameters viz. pH, SAB dose, and contact time in the range of 5–8, 2–7 g/L, and 60–120 min, respectively, following the experimental matrix developed by central composite design approach. SAB was characterized by scanning electron microscopy, Fourier transform IR spectroscopy and X‐ray diffraction to prevail the physical properties and detect the surface contexture. At a fixed initial concentration of 10 mg/L for the synthetic solution, the maximum removal was 83.04% at pH 6.5, contact time 90 min, SAB dose 8.7 g/L, temperature 30 °C and 300 rpm, while for the sample collected from Asanjola it was 81.3% for the initial concentration of 7 mg/L under the same process conditions. The significance of process parameters was checked by analysis of variance and a regression model was derived. The results of the study revealed that the SAB indigenously prepared from C. nucifera shell could be an eminent adsorbent for the defluoridation of water. Abstract : The indigenously prepared biochar from Cocos nucifera shell is a potential adsorbent for the defluoridation of water in a slightly acidic environment (pH 6.5). The implication of the process specification was checked by ANOVA and a regression model was derived. The maximum removal achieved was 81.3% with an initial F − concentration of 7 mg/L of the collected samples.